Construct validity of creative thinking skills instrument for biology student teachers in the subject of human physiology - Pada, Andi Ulfa Tenri; Mustakim, Siti Salina; Subali, Bambang (Jurnal Penelitian dan Evaluasi Pendidikan, 2018)
This article discusses the construct validity of the creative thinking skill instrument supporting a conation idea aspect for biology student-teachers in the subject of Human Physiology. Two hundred and eighteen students participated in this study. Construct validity was obtained through Confirmatory Factor Analysis technique  (CFA). Reliability was estimated by composite reliability. Findings show that the construct validity and the reliability of the instrument are high. A thorough discussion on the findings and future implications are provided towards the end of this paper.